HUBUNGAN MOTIVASI IBU DAN PERAN KADER DENGAN KEIKUTSERTAAN IBU DALAM KELAS IBU HAMIL - Wahyuni, Dian Putri; Sihombing, Sarmauli Franshisca (Universitas Batam, 2020)
The mortality rate of childbearing women in Indonesia is still significantly high. This situation urges the government to take action to overcome the problem by providing and spreading information and raising awareness on maternity health and childcare with the hope it will improve their knowledge and deepen their understanding. As such, antenatal class program is designed to accommodate the goal in surmounting childbearing women mortality issues in the immediate future. This research aims to discover the correlations between pregnant womenâ€™s interest and health cadre role on the participation in attending antenatal class. It was conducted in the coverage area of Puskesmas (community clinic) Batu Aji, Batam, from February to July 2019. The research design employs analytic descriptive method with cross-sectional approach by applying simple random sampling technique on the total sample population of 82 pregnant women. The research instrument is in the format of questionnaire. The data analyzing technique employs univariate and bivariate with chi-square where the significance level tolerance Ï-value < (Î±) 0.05. The findings reveal that the interest to attend the class is notably high with 77 (93.9%) respondents asserting; health cadre role in advocating them to comply is also highly significant with 76 (92.7%) respondents affirming; and the participation of pregnant women in attending the class is 47 (57.3%) respondents confirming in presence. The chi-square findings reveal the correlation between pregnant womenâ€™s interest and their participation in attending the class is indicated by Ï-value = 0.018, while the correlation between the health cadre role and the participation in attending the class is indicated by Ï-value = 0.017; these confirm the correlations between pregnant womenâ€™s interest and health cadre role on their participation in attending antenatal class. In suggestion, with some insights provided from this research, more health cadres are encouraged to help and motivate pregnant women to attend antenatal class because it can beneficially help improve their health and physical wellness.